2023
DOI: 10.3389/fphar.2023.1129817
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of baicalin for respiratory diseases: an update and future perspectives

Abstract: Background: Respiratory diseases are common and frequent diseases. Due to the high pathogenicity and side effects of respiratory diseases, the discovery of new strategies for drug treatment is a hot area of research. Scutellaria baicalensis Georgi (SBG) has been used as a medicinal herb in China for over 2000 years. Baicalin (BA) is a flavonoid active ingredient extracted from SBG that BA has been found to exert various pharmacological effects against respiratory diseases. However, there is no comprehensive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“… 19 , 88 When nanoparticles enter the lungs, they may be transferred to other organs by other means, such as the blood, causing damage to other organs. 89 The potential toxic effects of nanoparticles within the lungs may depend on the particle surface chemistry and size, and research has indicated that smaller nanoparticles can reduce their toxicity to some extent, cause them to metabolize better in the body, and reduce damage to the body. 90 , 91 …”
Section: Pharmacokinetics and Toxicology Of Inhaled Nano-formulationsmentioning
confidence: 99%
“… 19 , 88 When nanoparticles enter the lungs, they may be transferred to other organs by other means, such as the blood, causing damage to other organs. 89 The potential toxic effects of nanoparticles within the lungs may depend on the particle surface chemistry and size, and research has indicated that smaller nanoparticles can reduce their toxicity to some extent, cause them to metabolize better in the body, and reduce damage to the body. 90 , 91 …”
Section: Pharmacokinetics and Toxicology Of Inhaled Nano-formulationsmentioning
confidence: 99%
“…Baicalin, a flavonoid isolated from the roots of Scutellaria baicalensis Georgi (Lamiaceae), has been primarily used in traditional Chinese Medicine ( Srinivas, 2010 ). Baicalin has been reported to treat different diseases via exerting its various functions, such as anticancer, antioxidant, antiviral, anti-inflammatory effects ( Li et al, 2021 ; Ganguly et al, 2022 ; Song et al, 2023 ; Wang and Li, 2023 ). Baicalin has shown its protective functions in OA pathological process.…”
Section: Introductionmentioning
confidence: 99%